Basics of Ensuring Gender Equality and an Ecological Business Environment through the Development of Women's Entrepreneurship - Kamaldinovna, Yakubova Nigora (American Journal of Biomedicine and Pharmacy, 2025)
This article analyzes the development of women's entrepreneurship as a key factor in promoting gender equality and fostering an environmentally sustainable business environment. Supporting female entrepreneurs contributes significantly to socio-economic stability and aligns with sustainable development goals. The study employs various research methodologies, including statistical analysis, SWOT analysis, PEST analysis, expert surveys, and regression analysis. The findings highlight the increasing role of women-led businesses in economic growth and environmental sustainability, as well as the challenges they face, such as limited financial resources, regulatory barriers, and market competition. The paper also provides recommendations for enhancing female entrepreneurship and integrating green business practices into their operations.